Modeling the Holocaust: Models of Crematoria and Death Camps - Łysak, Tomasz (Holocaust and genocide studies, 2025)
Memorial museums frequently use models of the crematoria and death camps to help visitors visually represent aspects of the Holocaust; however, scholars in the field of Holocaust studies have often ignored or marginalized these representational strategies. This article analyzes dioramas, architectural models, maquettes, and miniatures in relation to their materiality and mediality. It historically surveys key seminal models including Mieczysław Stobierski's model of Crematorium II at Auschwitz-Birkenau, and Jankiel Wiernik's model of Treblinka. The author assesses these works' contribution to the field's understanding of the Holocaust as an industrialized killing process, which the Nazis perpetrated in purpose-built environments. Using an arts-based analytical approach, the author demonstrates these objects' multifaceted functions as works of art, historical evidence, didactic props, and invisible objects.